Effects of a low-sodium diet in patients with idiopathic hyperaldosteronism: a randomized controlled trial - Zhou, Lihua; Jiang, Yiran; Zhang, Cui; Su, Tingwei; Jiang, Lei; Zhou, Weiwei; Zhong, Xu; Wu, Luming; Wang, Weiqing (Frontiers in Endocrinology, 2023)
Background: Idiopathic hyperaldosteronism (IHA) is one of the most common types of primary aldosteronism (PA), an important cause of hypertension. Although high dietary sodium is a major risk factor for hypertension, there is no consensus on the recommended dietary sodium intake for IHA. Objective: This study investigated the effect of a low sodium diet on hemodynamic variables and relevant disease biomarkers in IHA patients, with the aim of providing a useful reference for clinical treatment. Methods: Fifty IHA patients were evenly randomized into two groups and provided, after a 7-day run-in period (100 mmol/d sodium), either a low sodium diet (50 mmol/d sodium) or a normal sodium diet (100 mmol/d sodium) for an additional 7 days. After the 14-day intervention (conducted without potassium supplementation), changes in blood pressure (BP) and serum potassium were evaluated in both groups. Results: After the dietary intervention, the low sodium group exhibited, compared to the normal sodium group, decreased BP (SBP: 121.8±12.8 vs. 129.9±12.1 mmHg, P<0.05; DBP: 82.6±7.6 vs. 86.4±8.2 mmHg, P<0.05; MAP: 95.7±8.8 vs. 100.9±8.4 mmHg, P<0.05) and increased serum potassium levels (3.38±0.33 vs. 3.07±0.27 mmol/L, P<0.001). The low sodium group showed also better control of both BP and serum potassium: BP <140/90 mmHg in 70.0% of total patients (76.0% vs. 64.0%, in the low and normal sodium groups, respectively; P>0.05), BP <130/85 mmHg in 38.0% of total patients (56.0% vs. 20.0%, P<0.05), BP <120/80 mmHg in 28.0% of total patients (44.0% vs. 12.0% , P<0.05); serum potassium ≥3.5 mmol/L in 22.0% of total patients (32.0% vs. 12.0% in the low and normal sodium groups, respectively; P=0.088). There were differences between the controlled BP group (<120/80 mmHg) and the non-controlled BP group (≥120/80 mmHg) in gender, BP at baseline, and type of diet (low vs normal sodium). Female gender and low sodium diet were protective factors for BP control. Conclusions: A low sodium diet is effective in lowering BP and elevating serum potassium in IHA patients. Female patients on a low sodium diet are more likely to achieve BP control (<120/80 mmHg). We advocate a dietary sodium intake of 50 mmol/d for IHA patients.